Effects of ph in mercury nitrate treatment using membrane system with biological pretreatment - Mohd Yusnizam, Yusof (2008)
Wastewater come from industry containing mercury is very dangerous. We need to treat the wastewater effectively to avoid the toxic. Membrane usage in wastewater treatment has increase due to its ability to filtrate the unwanted particle. The manipulating of parameters of membrane can give the better result other then changing the type of membrane for filtration of mercury in wastewater. Using P.putida as the pretreatment or volatilizing agent and continue with alternation of pH value for mercury solution, this technique seems easily can reach the target of removing mercury to the minimum level of permitted. According to experiment, the pretreatment stage decreases the Hg solution from concentration of 250ppb to 8ppb. Then, continue with Membrane separation, the concentration was decrease to 0ppb within pH8 to pH9. So, as conclusion, the best pH for operating membrane to filtrate mercury wastewater is pH8 to 9. This is because membrane operates at neutral or base condition.